Social Impact of Reforms and Expansion of Foreign Companies in Indian Retail Industry: The growth and challenges of the Indian retail industry (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The retail industry is an economic field that involves individuals and businesses that sell finished goods to end-users. In the United States, multi-store supermarket chains are both traded publicly on the stock market and are private. Retailing is also a core element of India's economic development, accounting for approximately 10 percent of its GDP. The Indian retail sector is one of the world's top cinq retail markets, valued at 600 billion US dollars, by economic value. Indeed, India's top ten retail companies have more than 1,000 departmental outlets, and this group of Indian retail companies employs over 7,500. The retail industry has emerged in India with many players coming into the market as one of the competitive and quickest industries. However, they all have not yet tasted success due to the heavy initial investments needed to split and compete with other firms. India's retail sector is rapidly turning into the next booming industry.